Digital Vigilantism and Cybersecurity: When the Public Takes Over Digital Law Enforcement - Flora, Heny Saida; Arifah, Heni Inayatul (PT. Hafasy Dwi Nawasena, 2026)
The proliferation of digital technologies has engendered a distinctive socio-legal phenomenon wherein private citizens and non-state actors increasingly assume quasi-enforcement roles in the digital realm, a practice broadly characterized as digital vigilantism. This article examines the legal, ethical, and cybersecurity dimensions of digital vigilantism, with particular emphasis on its implications for the rule of law, due process guarantees, and the institutional integrity of state-based law enforcement. Employing a normative legal analysis combined with a systematic review of contemporary scholarly literature published between 2021 and 2025, this study identifies and critically appraises six principal forms of digital vigilantism—namely paedophile hunting, hacktivism, open-source intelligence (OSINT) investigations, social media shaming, cyber-fraud counter-operations, and organized digital patrols—across multiple jurisdictions including Indonesia, India, China, Russia, the United Kingdom, and the European Union. The findings reveal a persistent doctrinal tension between the perceived legitimacy of public digital enforcement and fundamental legal principles including presumption of innocence, the prohibition of arbitrary punishment, and privacy rights. This article argues that the absence of a coherent regulatory framework governing digital vigilantism constitutes a significant lacuna in contemporary cybersecurity governance, and proposes a multi-layered co-regulatory model that balances civic participation with institutional accountability. The study contributes to the nascent body of comparative digital law scholarship and offers actionable policy recommendations for legislators, law enforcement agencies, and civil society organizations.